A study on the luminescence properties of gamma-ray-irradiated white light emitting Ca2Al2SiO7:Dy3+ phosphors fabricated using a combustion-assisted method. Issue 55 (18th May 2016) - Tiwari, Geetanjali; Brahme, Nameeta; Sharma, Ravi; Bisen, D. P.; Sao, Sanjay K.; Dhoble, S. J.
Abstract : Ca2 Al2 SiO7 :Dy 3+ phosphors emitting long-lasting white light were synthesized by a combustion-assisted method. Abstract : Ca2 Al2 SiO7 :Dy 3+ phosphors emitting long-lasting white light were synthesized by a combustion-assisted method. The phase structure, surface morphology, particle size, and elemental composition were analysed using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX) techniques. The XRD profiles showed that all peaks could be attributed to the tetragonal Ca2 Al2 SiO7 phase when the sample was annealed at 1100 °C for 4 hours. The thermoluminescence (TL) intensity increased with increasing γ-dose and it seemed to become saturated at 1180 Gy. The increase in TL intensity indicates that the concentration of traps increased with the γ-dose. Moreover, the depths and frequency factors of the trap centers were calculated from the TL glow curve of the sample, which indicated that the trap centers corresponding to the 420 K (1st peak) and 462 K (2nd peak) band were more helpful to long-lasting phosphorescence. Under γ-excitation, the TL emission spectra of the Ca2 Al2 SiO7 :Dy 3+ phosphor showed the characteristic Dy 3+ emission peaks at 484 nm (blue), 583 nm (yellow), and 680 nm (red), originating from the transitions 4 F9/2 → 6 H15/2, 4 F9/2 → 6 H13/2, and 4 F9/2 → 6 H11/2, respectively. Photoluminescence (PL) decay is also reported and it indicates that the Ca2 Al2 SiO7 :Dy 3+ phosphor shows fast and slow decay processes. The effect of the doping concentration on the crystal structure and the luminescence properties of the Ca2 Al2 SiO7 :Dy 3+ phosphors was investigated. The peak for the mechanoluminescence (ML) intensity increases linearly with the increasing impact velocity of the moving piston. The possible mechanisms of the TL, PL, and ML of the white light emitting long-lasting phosphor are also discussed.